Effect of reduction time on the structure and properties of porous graphene. (12th July 2017) - Li, Guoping; Zhang, Chenhui; Zhang, Tianfu; Xia, Min; Luo, Yunjun
Abstract: Porous graphene with nanoscaled pores on the sheets was prepared by a carbon thermal reduction method, in which the molybdenum oxide nanoparticles generated from the thermal decomposition of molybdate were used as the etching reagent, and the pores were formed on the surface of the reduced graphene oxide under the conditions of 650 °C and a nitrogen atmosphere. The morphology of pores on the graphene sheets may affect their potential applications in various fields, especially in the enhancement of mass transfer. Previous studies have shown that the reduction temperature and the amount of metal oxide are the key factors affecting the morphology of porous graphene, but in fact the reduction time is a more important affecting factor according to the present study. The results of SEM/TEM showed that a disordered large sheet-like structure with wrinkles was obtained at 120 min in the carbon-thermal reaction. The structural integrity of the PG was further destroyed after the reaction time of 140 min, in which the edge exhibited slightly crush and significant fold. The PG exhibited a hollow rod-like structure at the reaction time of 180 min. FTIR, Raman, XRD, and XPS studies were performed to characterize the morphology of porous graphene prepared at different reduction times.